2015
DOI: 10.1038/srep14552
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the Plasmodium falciparum chloroquine resistance transporter, PfCRT, enlarge the parasite’s food vacuole and alter drug sensitivities

Abstract: Mutations in the Plasmodium falciparum chloroquine resistance transporter, PfCRT, are the major determinant of chloroquine resistance in this lethal human malaria parasite. Here, we describe P. falciparum lines subjected to selection by amantadine or blasticidin that carry PfCRT mutations (C101F or L272F), causing the development of enlarged food vacuoles. These parasites also have increased sensitivity to chloroquine and some other quinoline antimalarials, but exhibit no or minimal change in sensitivity to ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
58
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 70 publications
(107 reference statements)
7
58
0
Order By: Relevance
“…3; Table S1), consistent with the appearance of this mutation in the AMT-resistant FCB C101F parasites (69). Our data also documented a 2-fold increase in the BSD IC 50 s of Dd2 Dd2+C101F clones compared to Dd2 Dd2 ( P < 0.001).…”
Section: Resultssupporting
confidence: 77%
“…3; Table S1), consistent with the appearance of this mutation in the AMT-resistant FCB C101F parasites (69). Our data also documented a 2-fold increase in the BSD IC 50 s of Dd2 Dd2+C101F clones compared to Dd2 Dd2 ( P < 0.001).…”
Section: Resultssupporting
confidence: 77%
“…These mutations include K76T, ubiquitous to all CQ-resistant alleles irrespective of origin and a sensitive marker of in vivo CQ treatment failure (Supplementary Table 1). In addition, several novel PfCRT mutations have been observed that can revert parasites to a CQ-sensitive status despite the presence of K76T, including C101F—which arose under pip-eraquine (PPQ) or amantadine pressure in vitro 42,166 —or C350R, which has recently spread throughout French Guiana 167 . Some PfCRT variants also mediate resistance to the active metabolite of AQ (monodesethyl-AQ), which might have been an important driving force for selection 168,169 .…”
Section: Multidrug Resistance (Mdr)mentioning
confidence: 99%
“…It was demonstrated that P. falciparum lines subjected to selection by amantadine or blasticidin carried the mutations in PfCRT (C101F or L272F) resulting in the enlargement of the parasite's food vacuole and alter the drug sensitivity, manifested by increased susceptibility to choloroquine and other quinoline antimalarials [50]. The swollen DV may be accounted for by presence of mutations interfering with the transport of the natural substrates of PfCRT out of the food vacuole, resulting in increased osmotic pressure in the food vacuole.…”
Section: Discussionmentioning
confidence: 99%
“…Two independent genome-wide association studies (GWAS) showed that amplification of the PM2 gene was associated with reduced PPQ sensitivity [19,20]. Targeted gene disruption of either PM2 or PM3 in P. falciparum 3D7 background accounted for a slight decrease in PPQ IC 50 value, but a significantly increased sensitivity to PPQ in a modified PSA [28]. However, the overexpression of PM2 and PM3 in the 3D7 genetic background did not alter the sensitivity of P. falciparum to PPQ, suggesting that the increase in PM2 copy number alone is not the sole modulator of PPQ resistance [29].…”
Section: Introductionmentioning
confidence: 99%